Skip to main content
Solve for t
Tick mark Image

Similar Problems from Web Search

Share

11=-10t^{2}+44t+30
Multiply 11 and 1 to get 11.
-10t^{2}+44t+30=11
Swap sides so that all variable terms are on the left hand side.
-10t^{2}+44t+30-11=0
Subtract 11 from both sides.
-10t^{2}+44t+19=0
Subtract 11 from 30 to get 19.
t=\frac{-44±\sqrt{44^{2}-4\left(-10\right)\times 19}}{2\left(-10\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -10 for a, 44 for b, and 19 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
t=\frac{-44±\sqrt{1936-4\left(-10\right)\times 19}}{2\left(-10\right)}
Square 44.
t=\frac{-44±\sqrt{1936+40\times 19}}{2\left(-10\right)}
Multiply -4 times -10.
t=\frac{-44±\sqrt{1936+760}}{2\left(-10\right)}
Multiply 40 times 19.
t=\frac{-44±\sqrt{2696}}{2\left(-10\right)}
Add 1936 to 760.
t=\frac{-44±2\sqrt{674}}{2\left(-10\right)}
Take the square root of 2696.
t=\frac{-44±2\sqrt{674}}{-20}
Multiply 2 times -10.
t=\frac{2\sqrt{674}-44}{-20}
Now solve the equation t=\frac{-44±2\sqrt{674}}{-20} when ± is plus. Add -44 to 2\sqrt{674}.
t=-\frac{\sqrt{674}}{10}+\frac{11}{5}
Divide -44+2\sqrt{674} by -20.
t=\frac{-2\sqrt{674}-44}{-20}
Now solve the equation t=\frac{-44±2\sqrt{674}}{-20} when ± is minus. Subtract 2\sqrt{674} from -44.
t=\frac{\sqrt{674}}{10}+\frac{11}{5}
Divide -44-2\sqrt{674} by -20.
t=-\frac{\sqrt{674}}{10}+\frac{11}{5} t=\frac{\sqrt{674}}{10}+\frac{11}{5}
The equation is now solved.
11=-10t^{2}+44t+30
Multiply 11 and 1 to get 11.
-10t^{2}+44t+30=11
Swap sides so that all variable terms are on the left hand side.
-10t^{2}+44t=11-30
Subtract 30 from both sides.
-10t^{2}+44t=-19
Subtract 30 from 11 to get -19.
\frac{-10t^{2}+44t}{-10}=-\frac{19}{-10}
Divide both sides by -10.
t^{2}+\frac{44}{-10}t=-\frac{19}{-10}
Dividing by -10 undoes the multiplication by -10.
t^{2}-\frac{22}{5}t=-\frac{19}{-10}
Reduce the fraction \frac{44}{-10} to lowest terms by extracting and canceling out 2.
t^{2}-\frac{22}{5}t=\frac{19}{10}
Divide -19 by -10.
t^{2}-\frac{22}{5}t+\left(-\frac{11}{5}\right)^{2}=\frac{19}{10}+\left(-\frac{11}{5}\right)^{2}
Divide -\frac{22}{5}, the coefficient of the x term, by 2 to get -\frac{11}{5}. Then add the square of -\frac{11}{5} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
t^{2}-\frac{22}{5}t+\frac{121}{25}=\frac{19}{10}+\frac{121}{25}
Square -\frac{11}{5} by squaring both the numerator and the denominator of the fraction.
t^{2}-\frac{22}{5}t+\frac{121}{25}=\frac{337}{50}
Add \frac{19}{10} to \frac{121}{25} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(t-\frac{11}{5}\right)^{2}=\frac{337}{50}
Factor t^{2}-\frac{22}{5}t+\frac{121}{25}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(t-\frac{11}{5}\right)^{2}}=\sqrt{\frac{337}{50}}
Take the square root of both sides of the equation.
t-\frac{11}{5}=\frac{\sqrt{674}}{10} t-\frac{11}{5}=-\frac{\sqrt{674}}{10}
Simplify.
t=\frac{\sqrt{674}}{10}+\frac{11}{5} t=-\frac{\sqrt{674}}{10}+\frac{11}{5}
Add \frac{11}{5} to both sides of the equation.